2010
DOI: 10.1021/jp9098792
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Hydrogen Migration in Alkylperoxy and Hydroperoxyalkylperoxy Radicals: Accurate Treatment of Hindered Rotors

Abstract: We have calculated the thermochemistry and rate coefficients for stable molecules and reactions in the title reaction families using CBS-QB3 and B3LYP/CBSB7 methods. The accurate treatment of hindered rotors for molecules having multiple internal rotors with potentials that are not independent of each other can be problematic, and a simplified scheme is suggested to treat them. This is particularly important for hydroperoxyalkylperoxy radicals (HOOQOO). Two new thermochemical group values are suggested in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
400
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 239 publications
(438 citation statements)
references
References 63 publications
(132 reference statements)
36
400
0
2
Order By: Relevance
“…The weak O-OH bond in the ketohydroperoxide then breaks to form OH and an alkoxy radical. This sequence of chain branching reactions is responsible for low-temperature reactivity 10 .…”
Section: Update 8: Isomerization Of Ooqooh (Ooqooh ↔ Ketohydroperoxidmentioning
confidence: 99%
See 3 more Smart Citations
“…The weak O-OH bond in the ketohydroperoxide then breaks to form OH and an alkoxy radical. This sequence of chain branching reactions is responsible for low-temperature reactivity 10 .…”
Section: Update 8: Isomerization Of Ooqooh (Ooqooh ↔ Ketohydroperoxidmentioning
confidence: 99%
“…However, Sharma et al 10 found that the difference between the activation energies of RO 2 isomerization and OOQOOH isomerization varies with the transition state's ring size. They estimated corrections of 8.6, 2.2 and 0 kcal/mol for 5-, 6-and 7-membered ring migrations, respectively.…”
Section: Update 8: Isomerization Of Ooqooh (Ooqooh ↔ Ketohydroperoxidmentioning
confidence: 99%
See 2 more Smart Citations
“…[140] Examples for typical reaction classes are hydrogen abstraction from the fuel molecule by different radicals or O 2 addition to the different fuel radicals,and each reaction class typically leads to an umber of elementary reactions.T hese reaction classes are applied consistently to species of different size,a nd Arrhenius parameters for the reaction rate coefficients are then assigned by so-called rate rules that depend on the reaction class and the specific sites at which the reaction occurs.Useful and accurate sets of reaction classes and associated rate rules have been published in the Angewandte Chemie Reviews recent literature. [153][154][155][156] Ab initio calculations to determine reliable bond dissociation energies,r eaction rate parameters for the most decisive reactions such as the initial hydrogen abstraction from the fuel, transition states,a nd branching ratios towards specific products are valuable complements to such efforts.…”
Section: Mechanism Developmentmentioning
confidence: 99%